Morphometric comparison in populations of melipona beecheii of the municipality of Cienfuegos (2022)
The study of the morphometric characters allowed to identify the similarities and differences between two populations ofstingless bee Melipona beecheii of the municipality of Cienfuegos. To study the morphometric affinities, 15 to 20 young workers from the breeding chamber were selected and preserved in absolute ethanol at -20°C for subsequent analysis inthe microbiology laboratory of the Faculty of Agricultural Sciences of the University of Cienfuegos. The evaluation of 12 morphological characters, 8 did not present significant differences, except for the width of the head (CA) 5.016 ± 0.014, the length of the head (4.311 ± 0.024) and length of the femur (4.398 ± 0.022) which were slightly greater for samples of themeliponary located in Pepe Rivas compared to the samples of Reina, where only difference was shown in the length of the tibia (4.075 ± 0.028). The degree of cephalic maculation of two populations of bees studied shown a degree of coloration in the middle, range in which yellow markings cover between 10 - 50% of the clypeus and supraclypeal area and extend as thinlines in the malar area around the eyes. The results of the morphological analysis and the degree of cephalic maculationsuggest that the populations of Melipona beecheii of Cienfuegos are similar to those studied in western Cuba and Yucatan.